Differences in polarization index of elite and subelite adult cyclists during a 12-month training cycle - Cove, B.; Bennett, H.; Nelson, M. J.; Chalmers, S. (International Journal of Sports Physiology and Performance, 2025)
Objectives: Training-intensity distribution among cyclists is pivotal. Polarized training (POL), characterized by an 80%/20% distribution between low and high intensities, is often considered the preferred model. This study compared polarization index (Pi) values between elite and subelite cyclists and evaluated the relationship between Pi and 20-minute power changes over 12 months.